Exploring the polygenic landscape of wool traits in Turkish Merinos through multi-locus GWAS approaches: middle Anatolian Merino - Yalçın Yaman; A. Taner Önaldi; Şükrü Doğan; Mesut Kirbaş; Sedat Behrem; Yavuz Kal (Scientific Reports)
Abstract This study investigates the genetic underpinnings of wool traits, specifically fibre diameter (FD) and staple length (SL), in Middle Anatolian Merino sheep using multi-locus genome-wide association study (GWAS) approaches. Representing the first attempt to examine these polygenic traits with multi-locus methods, the analysis employed four techniques: mrMLM, FASTmrMLM, FASTmrEMMA, and ISIS EM-BLASSO. A total of 18 Quantitative Trait Nucleotides (QTNs) were identified for FD, with 7 co-detected by multiple methods, and 14 QTNs were identified for SL, with 5 co-detected by multiple methods. Post-hoc power analysis revealed high statistical power for both traits (FD: 0.95, SL: 0.91). Notably, three candidate genes—PTPN3, TCF4, and ZBTB8A—were found to be consistent with prior studies. Gene enrichment and pathway analyses reaffirmed the complex and multifactorial molecular mechanisms governing wool traits. These findings enhance our understanding of the polygenic nature of wool traits, shedding light on the intricate genetic regulation and pinpointing genomic regions potentially influencing wool physiology. By identifying specific QTNs associated with FD and SL, this research provides a foundation for elucidating the genetic mechanisms underlying these economically significant traits. Upon validation in diverse populations, these findings hold substantial promise for the application of marker-assisted selection (MAS) to improve wool traits.